Web-Visions: Repurposing digital traces to organize social attention - Anders Koed Madsen (Copenhagen Business School (CBS), 2013)
In the late 1990s, Google pioneered the idea of scraping and repurposing digital traces as a new form of data with which to understand people's preferences and behaviour. This way of generating empirical sensitivity towards the world can be termed digital methods and the last five years have seen such methods gain influence beyond the field of Internet search. Organizations of different kinds are increasingly mentioning the need to harness the intelligence of `big' digital datasets, and the social sciences have similarly been marked by suggestions to move away from established methods such as surveys and focus groups, and learn from the way Google and other companies have succeeded in turning big datasets into knowledge of social dynamics. By enabling new combinations of data and software and by providing new ways of searching, aggregating, and cross-referencing empirical datasets, it seems probable that the spread of digital methods will re-configure the way organizations, social scientists, and citizens `see' the world in which they live.
hdl:10398/8746
Keywords: 650